Provincial police reform in early Victorian England: Cambridge, 1835-1856 - Swift, Roger (Routledge studies in modern British history, 2021)
"The establishment of "New Police" forces in early-Victorian England has long attracted historical enquiry and debate, albeit with a general focus on London and the urban-industrial communities of the Midlands and the North. This original study contributes to the debate by examining the nature and process of police reform, the changing relationship between the police and the public, and their impact on crime in Cambridge, a medium-sized county town with a rural hinterland. It argues that the experience of Cambridge was unique, for the Corporation shared co-jurisdiction of policing arrangements with the University and this fractious relationship, as well as political rivalries between Liberals and Tories, impeded the reform process, although the force was certified efficient in 1856. Case-studies of the careers of individual policemen and of the crimes and criminals they encountered shed additional light on the darker side of life in early-Victorian Cambridge and present a different and more nuanced picture of provincial police reform during a seminal period in police history than either the traditional Whig or early revisionist Marxist interpretations implied. As such, it will support undergraduate courses in local, social, and criminal justice history during the Victorian period"--